The revitalisation of historical buildings as a factor shaping the development of sustainable cities - Rząsa, Krzysztof; Ogryzek, Marek (International Conference “Environmental Engineering”, 2017)
Many Polish cities have objects in them that have ceased to function in accordance with their intended use, for one reason or another. These are often post-industrial objects and former military facilities. As a result of the social, political and economic transformations that have taken place in Poland over the years after the Second World War, these objects have lost the meaning of their existence and functioning. Quite often such objects also have a historical character, which may, under Polish law, serve to hinder the possibility of them being reused. A well prepared revitalisation is often the only way for such objects to regain their earlier functionality, or gain a new one. Selected examples of the revitalisation of historic buildings located in Olsztyn (the capital of Warmia and Mazury, the Voivodeship in North-East Poland) were analysed by the authors in this article, and the effects of such actions, connected to the development of the city, were presented. The study included examples of the revitalisation of post industrial objects and former military facilities. The analysis was performed in the years 2010–2016. The history and previous functional status of the tested objects were presented, as well as their present form and function. The authors have performed a comprehensive analysis of the compliance of new functions of objects with the idea of the sustainable development of the city. The results show the extent to which the analysed activities comply with the principles of sustainable development, in social, economic and environmental terms.